2000
DOI: 10.1590/s0102-86502000000500002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mouse and rat lymphoproliferation by gangliosides

Abstract: Our previous study have demonstrated that Glycosphingolipids (GSLs) have an immunosuppressive effect on murine lymphoproliferation and IL-2 production. In the present study we examined the effect of a pool of Gangliosides (Gang) on spleen lymphocyte proliferation from either isogeneic strains of Wistar rats or BALB/c mice. Two hundred-fifty grams adult female isogeneic Wistar rats and 8-week-old BALB/c mice were used. The animals were sacrificed and the spleen harvested aseptically for cellular assays. Spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Thus we have been testing a pool of gangliosides, defining one specific group of glycolipids which showed similar lymphocyte proliferation inhibition. 10 The limitation of our study is that we have not yet evaluated other glycolipid groups or isolated components.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we have been testing a pool of gangliosides, defining one specific group of glycolipids which showed similar lymphocyte proliferation inhibition. 10 The limitation of our study is that we have not yet evaluated other glycolipid groups or isolated components.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies demonstrated that some immunosuppressive agents act on arterial injury by decreasing or delaying intimal hyperplasia, independent of the lesion. [1][2][3] Because Gang have been shown to have an immunomodulatory effect in various kinds of immune response [4][5][6] it should be expected that they might act by delaying intimal hyperplasia. Therefore, 3 weeks after injury, there was an increase in intimal layer thickening.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Furthermore, a delay in wound healing 7 and a decrease in delayed hypersensibility response were observed. 8 Therefore, we decided to examine the effect of a Gang pool on intimal hyperplasia in the early phase of femoral artery injury in rats.…”
Section: Microsurgery 21:170-172 2001mentioning
confidence: 99%
“…7 The development process was evaluated according to semiquantitative morphologic parameters in the intestinal wall. We found that gangliosides had immunomodulatory effects such as inhibiting lymphocyte proliferation and IL-2 synthesis, 8,9 which commonly occur in acute allograft rejection. Therefore, we decided to compare histopathological changes in fetal intestine isografts and allografts treated with gangliosides.…”
mentioning
confidence: 96%